Distinct Impacts of Land Use and Land Management on Summer Temperatures - Chen, Liang; Dirmeyer, Paul A. (Frontiers in Earth Science, 2020)
Land use has been recognized as an important anthropogenic forcing of climate change in recent studies. However, climatic effects of land management practices have been little discussed and compared to land-use impacts. As land-atmosphere interactions via surface fluxes are particularly strong during the warm season, we investigate the impacts of historical land use and present irrigation practices on summer temperatures in the Northern Hemisphere using the most recent version of Community Earth System Model. Our results suggest that historical land use leads to an overall cooling in the middle latitudes and a warming in the tropics, and the sign and magnitude of the changes in temperature depend on the type of land cover change. On the other hand, summer irrigation leads to a significant cooling over many irrigated areas due to enhanced evapotranspiration, and the local cooling is comparable to and even stronger than the land-use effects. Both land use and irrigation can also significantly influence the intensity and frequency of hot extremes. Land use shows stronger impacts during the night through ground heat flux feedback, while irrigation shows stronger impacts during the day through latent heat flux feedback. Our comparison demonstrates the importance of irrigation in local and regional climate, highlighting the necessity of considering such land management practices in future assessments of regional climate change and climate mitigation.